CHILD LITERATURE GENRE FORMULATION IN WALT DISNEY ANIMATION MOVIE - Lisma Linda; Tomi Arianto (Universitas Putera Batam, 2018)
This study examined the formulation of the child literature genre with data sources in the form of Walt Disney Animation Movie sellection. Tangled (2010), Brave (2012) and Frozen (2013) were the 3 films chosen as data in this paper. The approach used by researchers in this study is a popular literary approach to the genre of children's literature based on Cawelty theory and other supporting theories. Child literature was generally a work created for children in which the language and story were simpler and easier to understand with the aim of entertaining and educating children at their age; help children in developing imagination, able to understand the meaning of life, and able to distinguish human characters. But more than it, children literature also displayed something that was unrealistic but could be accepted by the child as something that was reasonable and acceptance in a film. It was due to the intelligence of the producers in determining the direction of production so that the people really feel satisfied. In this study, researchers found that although plot in popular works was presented with various kinds of innovations and creativity of producers, there were formulas that became conventions so that children's literature could be accepted as reasonableness so as to obscure the boundaries of reality and reality in literary works.